PENGAWASAN PEMERINTAH DAERAH TERHADAP URUSAN PEMERINTAHAN BIDANG PERIKANAN (KASUS SUMBERDAYA KELAUTAN DAN PERIKANAN) DI KABUPATEN ROKAN HILIR TAHUN 2018-2019 - Azizul Hakim; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Rokan Hilir Regency is one of the regencies in Riau Province which has abundant marine and fishery resource potential. Rokan Hilir was once the area with the largest fish production in the world. However, this achievement has continued to decline until now the title of the region with the largest fish production in the world has been released. Therefore, it is necessary to supervise the Regional Government in this case which is carried out by the Riau Province Marine and Fisheries Service through the Technical Implementation Unit for Control of Marine and Fisheries Resources Region 3 in maintaining the potential for marine and fisheries in the Rokan Hilir Regency area to be utilized for the benefit of the people.The purpose of this research is to determine the Regional Government's Controlling of Government Affairs in the Fisheries Sector (Case of Marine and Fisheries Resources) in Rokan Hilir Regency 2018-2019, as well as to find out what are the inhibiting factors of the Regional Government in conducting control. This research uses a qualitative approach with descriptive methods. In collecting data, the writer used interview and documentation techniques.The results of this research are to determine the Regional Government's Supervision of Government Affairs in the Fisheries Sector (Case of Marine and Fisheries Resources) in Rokan Hilir Regency which is carried out by the Department of Marine Affairs and Fisheries of Riau Province through the Technical Implementation Unit (UPT) of Marine and Fishery Resources Control in Riau Province. 3. UPT has the task of coordinating, facilitating and evaluating the Sub-Division of Administration, the Section for Control and Supervision of Marine and Fisheries Resources, the Cooperation Section for Marine and Fisheries Law Enforcement, and Functional Positions. Controlling carried out by UPT is in the form of Preventive Controlling and Repressive Controlling. Keywords : Preventive controlling, repressive controlling, cooperation in controlling.